Lessons from joint development for cartilage repair in the clinic. Issue 3 (25th August 2020) - Thorup, Anne‐Sophie; Dell'Accio, Francesco; Eldridge, Suzanne E.
Abstract: More than 250 years ago, William Hunter stated that when cartilage is destroyed it never recovers. In the last 20 years, the understanding of the mechanisms that lead to joint formation and the knowledge that some of these mechanisms are reactivated in the homeostatic responses of cartilage to injury has offered an unprecedented therapeutic opportunity to achieve cartilage regeneration. Very large investments in ambitious clinical trials are finally revealing that, although we do not have perfect medicines yet, disease modification is a feasible possibility for human osteoarthritis. Key Findings: Developmental processes are reactivated in adult skeletal tissues following injury and contribute to repair and homeostasis Some such processes, when dysregulated, can contribute to tissue damage Specific stem cells persist in the adult joint and can be recruited to the repair response by specific signals Harnessing the molecular response to injury has led to the identification of pharmacological targets for osteoarthritis and cartilage repair